Characterization of compressed bacterial cellulose nanopaper film after exposure to dry and humid conditions - Abral, Hairul; Chairani, Melati Krista; Rizki, Muhammad Dinul; Mahardika, Melbi; Handayani, Dian; Sugiarti, Eni; Muslimin, Ahmad Novi; Salit, Mohd Sapuan; Ilyas, R. A. (Elsevier, 2021)
This work investigates the effects of two different levels of humidity (RH 50% and 75%) on the characterizations of compressed bacterial cellulose nanopaper film. The film was prepared with different heat treatments; compression at 25 °C for 72 h and then at 100 °C for 24, 72 or 120 h. Maximum tensile strength (250.7 MPa) and tensile modulus (18.6 GPa) were measured on the film treated at 100 °C for 120 h and RH 50%. However, tensile strength and tensile modulus dropped by 53.6% and 75.8% respectively and elongation at break increased by 32% when this film was stored in more humid conditions (RH 75%). FTIR spectra and XRD patterns indicate changes of the deformed chain structure of the cellulose as more water was incorporated between the layers of the lattice after exposure to humidity.